The Vega advanced third generation posterior stabilized total knee arthroplasty system enables the restoration of range of motion for high demanding daily activities - A 5-years follow-up study. - Ludger Gerdesmeyer; Claudio Glowalla; Igor Lasic; Munjed Al Muderis; Matthias Weuster; Tim Klueter (PLoS ONE)
Background The Vega System® PS (Aesculap AG, Tuttlingen, Germany) is an advanced, third generation fixed implant that aims to mimic natural knee kinematics by optimizing pivotal motion while reducing surface stress. This study evaluated mid-term survival and clinical outcomes, including range of motion (ROM) of the modern posterior stabilized implant in order to analyse whether this biomechanically successful implant reaches good results in situ. Methods The first 100 patients to receive the Vega PS System for total knee arthroplasty were invited to take part in this single centre, single surgeon study. Of these, 84 patients were clinically assessed 5-6 years postoperatively. Data which was obtained during this follow-up examination included revision data, range of motion and clinical scores. Results The 5-year survival rate for exchange of any component was 97.6%, whereby two patients required replacement of the polyethylene gliding surface. Secondary patella resurfacing was performed in 7 patients. Significantly improved results in comparison to the preoperative state could be obtained at the follow-up: KOOS improved from 39.4 to 78.8, SF-12 PCS improved from 32.1 to 42 SF-12 MCS improved from 46 to 53.8 and patella pain improved from 2.7 to 0.3. The mean ROM of the 84 patients after 5 years was 133.1° and mean total KSS was 189.9. Discussion & conclusions This study demonstrates a high survival rate of the Vega PS System® and significant improvements in clinical outcomes 5 years after implantation. The obtained mean ROM indicates that this implant provides good flexibility of the knee joint, allowing a high number of activities. However, due to the rate of secondary patella implantation, routine resurfacing of the patella for all PS TKA cases is highly recommended. Clinical trials registration The study was registered at clinicaltrials.gov (NCT02802085).